Activation of Antioxidant Response Element in Mouse Primary Cortical Cultures with Sesquiterpene Lactones Isolated from Tanacetum parthenium - Fischedick, Justin T.; Standiford, Miranda; Johnson, Delinda A.; De Vos, Ric C. H.; Todorović, Slađana; Banjanac, Tijana; Verpoorte, Rob; Johnson, Jeffrey A. (Planta Medica, 2012)
Tanacetum parthenium produces biologically active sesquiterpene lactones (SL). Nuclear factor E2-related factor 2 (Nrf2) is a transcription factor known to activate a series of genes termed the antioxidant response element (ARE). Activation of Nrf2/ARE may be useful for the treatment of neurodegenerative disease. In this study we isolated 11 SL from T. parthenium with centrifugal partition chromatography and semipreparative HPLC. Compounds were screened in vitro for their ability to activate the ARE on primary mouse cortical cultures as well as for their toxicity towards the cultures. All SL containing the α-methylene-γ-lactone moiety were able to activate the ARE and cause cellular toxicity. The structure–activity relationship among the SL isolated indicates that the guaianolides were more active and when lacking the endoperoxide functionality less toxic then the germacranolides.
Keywords: Tanacetum parthenium; Asteraceae; nuclear factor E2-related factor 2; antioxidant response element; sesquiterpene lactones; parthenolide; centrifugal partition; chromatography